Mulberry (Morus alba L.) leaf polysaccharide ameliorates insulin resistance‐ and adipose deposition‐associated gut microbiota and lipid metabolites in high‐fat diet‐induced obese mice. Issue 2 (24th December 2021) - Zhao, Xin; Fu, Zhifei; Yao, Minghe; Cao, Yu; Zhu, Tongtong; Mao, Rui; Huang, Ming; Pang, Yafen; Meng, Xianghui; Li, Lin; Zhang, Boli; Li, Yuhong; et al.
Abstract: Dietary supplements are currently being used to ameliorate metabolic alterations via maintaining gut microflora balance. Mulberry leaf is known as medicine homologous food for its glucose‐ and lipid‐modulating properties. However, the effects of mulberry leaf polysaccharide (MP) on metabolic dysbiosis and gut microbiota are still poorly understood. After extraction and characterization, the beneficial effects of water‐soluble MP were evaluated in high‐fat diet‐induced obese mice. MP treatment could reduce adipose tissue, improve insulin resistance, and alleviate the pathological lesions in colon. Investigation of the underlying mechanism showed that MP modulated gut microbial community by 16S rRNA analysis and reversed the elevation of lipid indexes by plasma lipidomics analysis. Correlation analysis indicated that the abundance of seven key bacterial species and six lipids were closely associated with the metabolic traits, respectively. Overall, MP could ameliorate metabolic disorders, and modify the gut microbiota and lipids. This would greatly facilitate the utilization of MP as a functional food. Abstract : MP could ameliorate metabolic disorders and modify the gut microbiota and lipids. This would greatly facilitate the utilization of MP as a functional food.